[3+2] Cycloaddition of azide with aldehyde hydrazone through an aminyl radical-polar crossover strategy. Issue 6 (3rd January 2017) - Wu, Zhongkai; Xu, Pan; Zhou, Nengneng; Duan, Yingqian; Zhang, Muliang; Zhu, Chengjian
Abstract : A novel approach to obtain functionalized tetrazoles through an aminyl radical-power crossover strategy is reported. Abstract : A novel approach to obtain functionalized tetrazoles by a [3+2] cycloaddition of azide with aldehyde hydrazone is reported. This reaction features a broad substrate scope and mild reaction conditions through an aminyl radical-polar crossover strategy.